EVOLUÇÃO DECADAL DAS DUNAS FRONTAIS DO LITORAL SUL DO ESPÍRITO SANTO POR PROCESSOS EÓLICOS E GEOMORFOLÓGICOS - Oliveira, Chiara Folli de (2021)
South Espírito Santo foredune stability is evaluated with the change polygon method by overlapping satellite images and aerial photographs of six foredune segments, along 19km of coastline. Results indicate that foredune dynamics and shoreline position trends are deeply related, therefore foredunes can be used to monitor the shoreline change. Local wind patterns over the decade 2009-2019 are characterized by prevailing north easterly winds that favour foredune development but on the other hand, are responsible for erosional processes such as dune scarps and blowouts. Each segment of study shows a specific behaviour and a different degree of erosion and recovery with increase in wind speeds. In the study area, foredune morphological variability alongshore is marked by stable foredunes with prograding coastline and limited seasonal retreat and foredunes migrating inland. Foredunes morphological variability is explained by local geomorphology and morpho-dynamic that influence sediment transport and depositional patterns in the foredune system. The interpretation of morphological structures in acretional and erosional sections revealed using GPR, validates direct observations and foredune mobility data.